PROBLEMATIKA KERAGAMAN LATAR BELAKANG PENDIDIKAN MAHASISWA DAN KEBIJAKAN PROGRAM PEMBELAJARAN BAHASA ARAB - Setiyawan, Agung (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This study aims to determine the problem of learning in the Department of Arabic Language Education UIN Sunan Kalijaga caused by differences in the educational background of students, knowing the way students to catch up the knowledge and abilities of Arabic language, and formulating a package of learning policy that considers the different background of education. This was descriptive-qualitative and field research. Data were collected through questionnaires and interviews. The respondents were the students and head of the Department of Arabic Language Education UIN Sunan Kalijaga as a stakeholder. The results show there were at least 7 learning problems caused by the differences of students’ education background. There were 3 learning programs which proclaimed by the Department to overcome the problems and 5 steps offered to catch up the knowledge and ability of Arabic language.